Self-reported dyspareunia and outcome satisfaction after spontaneous second-degree tear compared to episiotomy: A register-based cohort study. - Mette L Josefsson; Sara Sohlberg; Cecilia Ekéus; Eva Uustal; Maria Jonsson (PLoS ONE)
Introduction Symptoms after second-degree tears and in particular episiotomies are common. Our aim was to investigate the prevalence and degree of dyspareunia and level of satisfaction with the outcome of the perineal repair after a spontaneous second-degree tear compared to an episiotomy. Further, we aimed to identify risk factors for dyspareunia and dissatisfaction with the outcome. Material and methods This register-based cohort study included 5 328 primiparous women who sustained a spontaneous second-degree tear (n = 4 323) or an episiotomy (n = 1005) between 2014 and 2019 in Sweden. The primary outcomes were self-reported degree of dyspareunia and level of satisfaction with the outcome of the perineal repair at one year. Data were collected from national health and quality registers and online questionnaires at eight weeks and one year. Logistic regression was used and results are presented by Odds Ratios (OR) with 95% confidence intervals (CI) after adjustment for age, body mass index and mode of delivery. Results 30.0% of women with a spontaneous tear and 29.1% of women with an episiotomy reported mild or moderate dyspareunia, while 2.4% of women with a spontaneous tear compared to 3.8% of women with an episiotomy reported strong or unbearable dyspareunia (aOR 1.5; CI 0.9-2.4). 73.4% of women with a spontaneous tear and 67.1% with episiotomy were satisfied or very satisfied with their outcome, while 6.7% with an episiotomy compared to 3.7% with a spontaneous tear were dissatisfied (aOR 1.8; CI 1.2-2.6). Postpartum infection, scar dehiscence, re-suturing and perineal pain at eight weeks were risk factors for dyspareunia and dissatisfaction at one year. Conclusions Approximately one-third of women with either a spontaneous tear or an episiotomy reported mild or moderate dyspareunia at one year, while strong or unbearable pain was uncommon in both groups. The majority of women were satisfied or very satisfied with the outcome although episiotomy more often predicted dissatisfaction.